Electronic commerce as a business strategy for beauty products towards the chilean market. Case of the company the well life company (2020)
Electronic commerce is causing fundamental changes in companies and commerce at an international level, facilitating transactions and increasing interaction between consumers and merchants, which is why companies are opting for an increasing use of the internet. In this research, the areas of opportunity generated in the Chilean market were analyzed from the elaboration of an export business plan in the marketing of beauty products to the Chilean market, through an electronic business model in the company The Well Life Company located in the city of Culiacan, Sinaloa, Mexico. The methodological paradigm addressed in this research was qualitative, descriptive, as a single case study, and the semi-structured interview was used as a tool. The company must take into account factors such as globalization, internet usage rates, necessary standards and government or private support, as well as take advantage of the virtues of electronic commerce. In conclusion, the Chilean market is technically feasible for the export of beauty products thanks to its location, the culture of the use of beauty products and the trends in purchases from both national and international stores through the internet. Keywords: international trade, e-commerce, business plan, exportation, business in Latin America. JEL Codes: D23, L81, L22, M1, M16 Received: 25/05/2020.  Accepted: 20/05/2020.  Published: 24/05/2020.